Maturity Assessment at SMEs Assisted by BUMDesma (Joint Village-Owned Enterprises) - Yudha Prasetyawan; Suparno Suparno; Maria Anityasari; Niniet Indah Arvitrida; Taufik Fajar Nugroho; Herman Pratikno; Rahmadhani Tasya Rahman; Inastika Nabilah (IPTEK Journal of Proceedings Series, 2023)
Enhancing the Small to Medium Enterprises (SME) Competency is a way to raise the chance of winning a global competition. The basic business profile should be provided as proof of the general foundation of being known as a mature business. This research provides a tool for the government to collaborate with academics to analyze SME performance. This tool is used for policy-making, and funding could be more accurate based on nearly objective criteria. This designed interface helps SMEs submit their business document online with their current self-assessment for production, marketing and all the business features. The preliminary object covers the three different cities in East Java Province. Based on the submitted document and data, academia and the government can do online assessments to complete the direct assessment through direct observations. The dashboard shows the performance based on overall equipment efficiency and adjusted indicator using a business model canvas.